Rate and Computational Studies for Pd‐NHC‐Catalyzed Amination with Primary Alkylamines and Secondary Anilines: Rationalizing Selectivity for Monoarylation versus Diarylation with NHC Ligands. Issue 62 (10th October 2019) - Lombardi, Christopher; Rucker, Richard P.; Froese, Robert D. J.; Sharif, Sepideh; Champagne, Pier Alexandre; Organ, Michael G.
Abstract: The relative rates of arylation of primary alkylamines with different Pd‐NHC catalysts have been measured, as have the relative rates of arylation of the secondary aniline product in an attempt to understand the key ligand design features necessary to have high selectivity for the monoarylated amine product. As the substituents on the N ‐aryl ring of the NHC increase in size, selectivity for monoarylation increases and this is further enhanced by chlorinating the back of the NHC ring. Computations have been performed on the catalytic cycle of this transformation in order to understand the selectivity obtained with the different catalysts. Abstract : Bulky Pd‐PEPPSI precatalysts perform arylation of alkyl amines with high fidelity for the mono coupled product and staunchly avoids (over) arylating the product aniline. This observation is a consequence of two key features: formation of global resting state A, and irreversible deprotonation of A pushing the mechanism through to reductive elimination.